THE HEAT SHOCK PROTEIN 70-2 GENE (RS1061581) ASSOCIATES WITH THE ACUTE OTITIS MEDIUM IN CHILDREN - Л. Сидорчук; О. Саковець (Неонатологія, хірургія та перинатальна медицина)
Acute otitis media (AOM) represents one of the most prevalent pediatric conditions worldwide. Affecting millions of children / adolescents each year, AOM constitutes a significant public health concern. Although the fundamental mechanisms underlying AOM development are understood, the molecular and genetic aspects of its pathogenesis remain insufficiently explored.